KLF4 overexpression protects against complement-mediated endothelial injury in transplant-associated thrombotic microangiopathy - Shuhui Jiang; Jiaqian Qi; Tingting Pan; Zhenzhen Yao; Siyi Lu; Yifei Han; Depei Wu; Yue Han (Haematologica)
Transplant-associated thrombotic microangiopathy (TA-TMA) is a severe complication of hematopoietic stem cell transplantation, marked by excessive complement activation, endothelial injury, and microangiopathy. Although complement blockade benefits some patients, effective prophylactic and therapeutic strategies remain scarce. Therefore, plasma samples from 20 TA-TMA patients and 1:1 matched control patients (matched by age, sex, underlying diagnosis, HLA compatibility, graft source, and donor–recipient ABO blood type) were measured for krüppel-like factor 4 (KLF4), complement proteins and endothelial injury markers. The mechanism was investigated both in vitro and in vivo. In this study, plasma analysis revealed that TA-TMA patients exhibit notably lower KLF4 levels compared to matched controls, as well as elevated endothelial injury markers. In vitro, increased KLF4 expression in human umbilical vein endothelial cells significantly reduced complement deposition and mitigated endothelial damage induced by TA-TMA plasma. Furthermore, KLF4 overexpression notably decreased apoptosis and preserved endothelial barrier integrity. In a mouse model of TA-TMA triggered by dimethyloxalylglycine, upregulation of KLF4 alleviated anemia, thrombocytopenia, and renal complement deposition, while diminishing endothelial inflammatory and thrombotic markers. Intriguingly, pravastatin treatment produced similar improvements. Mechanistic analyses using CUT&Tag, RNA sequencing, luciferase assays, and quantitative real-time PCR revealed that KLF4 binds to the CD46 promoter, enhancing its transcription and thus restraining complement activation in endothelial cells. These results identify KLF4 as a key negative regulator of complement-mediated endothelial injury in TA-TMA. This conclusion is supported by CD46 knockdown abolishing KLF4-mediated benefits, highlighting the therapeutic potential of targeting KLF4 or its downstream effectors, including CD46.